Evaluation of Financial Performance of PT Waskita Karya Tbk in the Infrastructure Sector: Financial Ratio Analysis 2021-2023 - Pahrudin, Asep; Suciati, Ranila (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to assess the financial performance of PT Waskita Karya Tbk, a prominent company in the infrastructure sector, over the 2021-2023 period. The evaluation employs a financial ratio approach, including Net Profit Margin (NPM), Return on Equity (ROE), Earnings Per Share (EPS), Price Earnings Ratio (PER), Price to Book Value (PBV), and Debt to Equity Ratio (DER). This approach seeks to provide a comprehensive overview of the company's profitability, market valuation, and solvency. The findings indicate a notable improvement in profitability indicators, particularly in 2023. Market value indicators, such as EPS, also recorded sharp growth, reflecting the company's operational efficiency; meanwhile, PER experienced a significant decline, indicating a rationalization of stock valuations in the market. On the other hand, solvency was reflected in an increase in PBV, although the DER ratio also increased, indicating a greater reliance on debt. Overall, this study concludes that PT Waskita Karya Tbk shows a significant improvement trend in financial performance, especially in profitability and market value. However, better debt management is needed to maintain financial stability.